Preparation and Application of Magnetite (Fe3O4) Nanoparticles by Co-precipitation Method for Removal Rhodamine B in Wastewater - Ganesha Antarnusa (International Journal of Hydrological and Environmental for Sustainability, 2022)
Fe3O4 coated with PEG has been successfully synthesized using co-precipitation method to reduce RhB. From the XRD results, it can be seen that all samples are Fe3O4 with the highest Miller index at (311). The crystallinity of Fe3O4 was maintained even though PEG was added. From the SEM-TEM analysis, it can be seen that the two samples have a uniform size distribution. Then, PEG can increase the dispersibility of the sample. From the FTIR analysis it was confirmed that there was PEG content in Fe3O4. From the results of the VSM analysis, it was confirmed that the sample has nearly superparamagnetic properties with a small Â value. Then, Fe3O4 and Fe3O4/PEG were used to remove RhB in water by magnetic separation process. From the results of the study, it was obtained that the optimum absorption occurred in several parameters, namely the initial concentration of RhB at 100 mg/mL, with a pH of 6, the dose of Fe3O4/PEG at 0.8 g/L and a contact time of 40 minutes at room temperature. At this optimum condition, the absorption has a color removal of 31.1%.